Luminescent Schiff-Base Lanthanide Single-Molecule Magnets: The Association Between Optical and Magnetic Properties - Long, Jérôme (Frontiers in Chemistry, 2019)
Luminescent Single-Molecule Magnets (SMM) belong to a new class of multifunctional molecule-materials that associate luminescence and slow relaxation of their magnetization within a single crystalline phase. We present in this mini-review the major advances that have been achieved in this new field over the last few years. More particularly, we will focus on the use of Schiff-base complexes in order to correlate magnetism and luminescence, as well as discussing the future outlooks of the field.